Building multi-tenant SaaS architectures - Golding, Tod (O'Reilly Media, Inc., 2024)
Software as a service (SaaS) is on the path to becoming the de facto model for building, delivering, and operating software solutions. Adopting the multi-tenant model of SaaS requires builders to take on a broad range of new architecture, implementation, and operational challenges. How data is stored, how resources are isolated, how tenants are authenticated, how microservices are built--these are all examples of areas that builders must consider when designing and creating SaaS offerings. This practical book equips SaaS builders and architects with a collection of patterns, strategies, and insights to help you bridge these technical and business challenges. Tod Golding, a global SaaS lead at AWS, provides you with an end-to-end view of SaaS architecture and development techniques for addressing the unique blend of challenges associated with building a robust SaaS solution that realizes its full potential.
Keywords: Application service providers; Computer service industry -- Customer services; Software support; Cloud computing; Computer technical support; Fournisseurs de services applicatifs; Services informatiques; Service à la clientèle; Dépannage informatique; Infonuagique